A dignidade do consumidor superendividado: estudo à luz da lei do superendividamento - Vieira, Lara Fernandes (2022)
This thesis contributes to the treatment of the over-indebtedness of individual consumers in Brazil, a serious economic and social issue of contemporary times. The scenario in question is that of the consumer society, since the acquisition of products and services constitutes its central and defining element, occupying a significant existential dimension in peoples lives. This fact stems from the dynamics established by the market of permanent stimulus to consumption, thus generating a culture of indebtedness. In this context, it is necessary to question whether the instruments available in the Brazilian legal system, notably those introduced by the Over-indebtedness Law, are adequate and sufficient to solve the problem. The answer to this question was pursued from the general objective outlined. This thesis points out alternatives for an effective solution to the over-indebtedness of individual consumers in Brazil, under the premise of human dignity, based on the analysis of current legislation, in particular the Over-indebtedness Law. Due to its complexity, a transdisciplinary dialogue was established between Law and Philosophy, Sociology and Economics, contrasting theoretical discussion with practical experience, using the deductive method, of a qualitative nature, to analyze the data obtained through bibliographic, documentary and jurisprudential research on the subject. For the study of the cases presented, field research was carried out, through participation in conciliation hearings between over-indebted consumers and their respective creditors, randomly chosen. It is assumed as a hypothesis that the treatment provided by the Over-indebtedness Law is insufficient for the effective resolution of the problem of Brazilian over-indebted consumers. It is concluded that, although this law represents a significant advance in the matter, it still needs adjustments so that it can effectively provide the fresh start of thousands of Brazilian over-indebted consumers, rescuing their dignity. It is, therefore, an unprecedented and relevant study that contributes with a thorough analysis of the issue of over-indebtedness and of the referred Law, in the light of human dignity, with the proposal of recommendations.